(3GdLOhd GdUaj ef GdHMQ Gdhais - (3gHI Gddg eMeO GdOjQjs
(3ChdgG (B:s
(3GdMeO ddg hLGeY eNJUQ gPG GdcJGH gHI Gddg eMeO GdOjQi TgQI hGdMfai ePgHkG, hLeYJ ef CQHYjf cJGHkG JGQjNkG dWja GdMLe s
(3BNQgG (B:s
(3GdCTQai Edi eOjfI GdbOS GdTQja SfI SJI hJSYjf hNHQ HPdc hGbhd ehdjfG GdSdWGf fUQg Gddg hCeOg HGdYeQ GdWhjd s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hHYV GdcdeGJ HGdMeQIs
(3HChdgG agQSJ ddehVhYGJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs